Analisis Pembuktian Isu Pengambilalihan Akun oleh Pihak Ketiga Aplikasi Zenly Melalui Pemberlakuan UU Perlindungan Data Pribadi - Velycia Debora Gloria (STIKes Ibnu Sina Ajibarang, 2024)
The era of technological development is accompanied by the ease of obtaining information, digital things need to be considered for their sustainability. The presence of the PAPA concept (Privacy, Accuracy, Property, Accessibility) helps to make companies and applications aware of maintaining information and carrying out digital responsibilities. Privacy is a dimension that focuses on protecting personal data. The social map application is a platform that makes it easy for users to share and find out the location of friends and family. With a total of 35 million monthly active users, the level of data security is increasingly vulnerable because many new users register their personal data into user data. Although only diagnosing cases of account takeovers, of course, action and literacy education are needed because the company is fully responsible. The analysis tool used in qualitative research is Mitmproxy. The Zenly application is the object of this study. The results of the study are proven diagnoses that account takeovers can occur due to low levels of security, thus violating the ITE Law article 26.